Implementación de un sistema de puesta a tierra para los Laboratorios del bloque B de la Universidad Técnica de Cotopaxi Extensión La Maná. - Abrigo Vivas, Jason Enrique (2023)
This project is based on a study using the tellurometer in different areas around the laboratories belonging to the Technical University of Cotopaxi La Maná Extension. This type of grounding system, like any element that performs a function, is exposed to deterioration due to the passage of time or corrosion factors, this can cause it to not function correctly, this indicates that it is vitally important to have this type of grounding system. Grounding systems since they guarantee a better useful life of our electrical and electronic equipment, they also provide better safety to people who are in the area. It was concluded that the result of the total resistance of the mesh is 8.861x10, an ideal value for the application of this system since according to the NEC regulations in section 250-56 In installations with sensitive equipment, it should be 5. 0 Ohms or less. The importance of proposing this type of implementation system accompanied by the necessary equipment to be able to carry out good data collection in different tests and areas within the Block B facilities, transmit in the most convenient way and the information obtained is effective.